Genetic analysis of production and reproduction traits in Jaffarabadi buffaloes - S. G. Gajjar,; P. H. Vataliya,; A. R. Ahlawat,; P. U. Gajbhiye, (Journal of Livestock Biodiversity, 2025)
Lactation records of 189 Jaffarabadi buffaloes maintained at Cattle Breeding Farm, JAU, Junagadh, over a period of20 years (1991-2010) were analysed for genetic analysis of some production and reproduction traits in Jaffarabadibuffaloes. The production traits included were 300-days milk yield, lactation length and peak yield, and thereproduction traits were calving interval and dry period to study the effects of non-genetic factors viz. period,parity and season of calving. Least squares analysis revealed that period of calving had highly significant effect (P≤0.01) on all the five traits under the study. Season of calving had highly significant effect (P≤0.01) on reproductiontraits, while non-significant effect (P>0.05) on production traits. Parity of calving had highly significant effect (P≤0.01) on 300-days milk yield and peak yield while non-significant effect (P>0.05) on lactation length, calvinginterval and dry period.